Struktur Musik Buka Lanse Dalam Adat Perkawinan Masyarakat Melayu Di Kabupaten Batanghari Propinsi Jambi - Sherli Junikasari; Muhammad Zulfahmi; Firman Firman (Institut Seni Indonesia Padangpanjang, 2024)
This research discusses the structure of traditional open-lance music which is classified as unique and rare, but is threatened with extinction if it is not preserved. This study aims to examine the structure of open lanse music and its inheritance system in Batanghari Regency. This study uses qualitative research methods with data collection techniques of observation, interviews, documentation, and field studies. Discussion and analysis of data using structural theory. Buka lanse is a poem sung by traditional leaders or both the bride and groom. Poetry opens lance philosophically means the bride and groom are officially husband and wife, and the groom has legally entered the bride's room. The musical structure begins with the playing of the Malay drum instrument, piul (violin) accordion, keyboard, and vocals in the form of free meters, repeatedly (repetition style) and logogenic. Contour melodies are a mixture of ascending and descending. Open lanse music is still maintained as the identity of the Jambi Malay community in general and in particular the Malay community in the Rengas Condong Village, Muara Bulian District, Batanghari Regency